2021
DOI: 10.1016/j.sjbs.2021.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Potential hepatoprotective effects of flavonoids contained in propolis from South Sulawesi against chemotherapy agents

Abstract: The use of doxorubicin and epirubicin as chemotherapy agent causes side effects such as liver damage due to oxidative stress by reactive oxygen species (ROS) that cause increased of ALT and AST level as liver parameter. One source of natural antioxidants as ROS neutralizer comes from flavonoid that contain in propolis. Most researchers claim that flavonoid can be used to protect the liver. The aim of this study was to test the hepatoprotective effect of flavonoid in propolis from South Sulawesi against doxorub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…As expected, several animal models of MAFLD and alcoholic fatty liver disease have revealed increases in AST and ALT levels ( Lívero et al, 2014 , 2016 ; Barbosa et al, 2020 ; Souza et al, 2020 ; Mendes et al, 2021 ). The therapeutic effects of medicinal plants in reversing this increase in markers of liver damage are well described in the literature, especially the beneficial effects of flavonoids, glycosides, and alkaloids ( Ling et al, 2020 ; Zhang et al, 2020 ; Han et al, 2021 ; Niu et al, 2021 ; Ore et al, 2021 ; Sahlan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, several animal models of MAFLD and alcoholic fatty liver disease have revealed increases in AST and ALT levels ( Lívero et al, 2014 , 2016 ; Barbosa et al, 2020 ; Souza et al, 2020 ; Mendes et al, 2021 ). The therapeutic effects of medicinal plants in reversing this increase in markers of liver damage are well described in the literature, especially the beneficial effects of flavonoids, glycosides, and alkaloids ( Ling et al, 2020 ; Zhang et al, 2020 ; Han et al, 2021 ; Niu et al, 2021 ; Ore et al, 2021 ; Sahlan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are many different types of flavonoids that are known as various effects on health. Therefore, flavonoid content can be used as a parameter or index in evaluating the quality of medicinal plant used [19]. Preliminary flavonoid screening of the extract revealed the presence of flavonoids in the extract, and the result of the phytochemical test has been summarized in Table 1.…”
Section: Preliminary Flavonoid Screeningmentioning
confidence: 99%
“…The probable mechanisms of hepatotoxicity are summarized in Figure 1. Furthermore, pharmacokinetics studies of DOX in patients with abnormal liver biochemistry tests have revealed that patients with reduced DOX clearance not only had an increased bilirubin level, but also revealed elevated levels of liver enzymes, such as aspartate aminotransaminase (AST) and alanine aminotransaminase (ALT) (8). Approaches to doxorubicin dosing in patients with impaired liver function are variable now.…”
Section: None Herbal Agents As Preventive and Therapeutic Measures Fo...mentioning
confidence: 99%